UJI EFEKTIVITAS EKSTRAK ETANOL DAUN KOPASANDA (Chromolaena odorata L.)TERHADAP KEMAMPUAN EPITELISASI PADA TIKUS (Rattus norvegicus) YANG DIINDUKSI LUKA BAKAR - Sukmawati, Sukmawati; Auliawati, Auliawati; Syasmar, Andi Mustagfira (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
Burns are injuries that are quite common. Severe types show a relatively high morbidity and degree of disability and the costs required for treatment are also high. Epithelialization is a tissue repair process with the growth of epithelium on the peeled surface. The research aimed to determine the effect and effective concentration of the ethanol extract of siam weed leaves (Chromolaena odorata L.) on the epithelialization effect of burn-induced rats. The research used 15 rats divided into 5 treatment groups, namely negative group (Sodium CMC), positive group (Lanakeloid®), ethanol extract of siam weed leaves group with concentrations of 10%, 20% and 40%. The induction of burns used a heat plate at a temperature of 100°C for 2 seconds on the back of the rats. The therapy was given twice a day for 28 days. The measurement of wound area was done on days -1, -3, -7, -9, -11, -14, -17, -21, -24, and -28. The data were statistically done using One Way Anova followed by further test of LSD (Least Significant Difference). The results showed that the positive control group was not significantly different from the extract given group with the concentrations of 10% and 20%, therefore, it can be concluded that the ethanol extract of siam weed leaves had an effect in accelerating the wound healing process in burn-induced rats with an effective concentration of 20%.